Memory reconsolidation impairment by amyloid beta (1–42) and its prevention by non-competitive antagonists of NMDA receptors - Tiunova, A. A.; Diffine, E. A.; Anokhin, K. V. (Frontiers in Cellular Neuroscience, 2025)
In a healthy brain, the reactivation of memories under conditions of novelty leads to their labilization and subsequent reconsolidation. However, if plasticity of the nervous system is reduced reconsolidation mechanisms may be disrupted, leading to weakening and loss of existing memory. We hypothesize that such self-degradation of old memory due to its reactivation in the compromised brain may lead to progressive memory loss in Alzheimer’s disease. Preventing memory lability when accessing it, may slow down such engram degradation. To test these hypotheses, we first examined whether beta-amyloid peptide Aβ1–42 can impair reconsolidation of memory in one-trial passive avoidance task in young chicks. Next, we examined the possibility to prevent such reminder-associated amnesia by administering a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist MK-801 prior to memory reactivation. Finally, we compared the memory protecting effects of two non-competitive NMDA antagonists, MK-801 and memantine which is a clinically used medication for treatment of Alzheimer’s disease. We found that administration of Aβ1–42 prior to memory reactivation in passive avoidance task in chicks impaired its subsequent reconsolidation. Concurrent systemic injection of MK-801 or memantine prevented this impairment. Our data thus support the hypothesis about the possible role of impaired reconsolidation in the progressive deterioration of old memories in neurodegenerative diseases, particularly in Alzheimer’s disease. This hypothesis offers a new explanation for the protective effects of memantine and suggests the possibility of similar effects with other NMDA receptor antagonists.